Marketing Communication in Increasing Sales in Media Ilmu Publishers of Sidoarjo - Afifah Dian Rahmanita; Panuju, Redi (GREENOMIKA, 2023)
Marketing communication is a company tool to inform, persuade, and remind consumers about the products and brands being sold. Media Ilmu Sidoarjo Publisher has a market segment in the form of books for Islamic schools/madrasas. The booming of Islamic books including books for Islamic schools/madrasas in the community creates new challenges for Sidoarjo Science Media Publishers. The purpose of this study is to describe marketing communications in increasing sales at Media Ilmu Sidoarjo Publisher, by implementing the marketing mix strategy / 4P which refers to the four Ps, namely product, price, promotion, and place. This study uses a qualitative descriptive research method, with data collection techniques by interviews, observation, and triangulation. Based on the results of the study, it was concluded: (i) a product strategy to maintain quality by implementing very strict quality control, (ii) a pricing strategy to attract consumers to buy with a policy of discount strategies and selling price discrimination, (iii) a strategy distribution using a zerolevel and two-level channel strategy. While the marketing channel (intermediary) uses a sales force (sales force) which is a direct marketing channel service and through wholesalers (distributors), (iv) the promotion strategy refers to the promotion mix which consists of advertising, personal selling, sales promotion, publicity and relations public. With these four strategies, Media Ilmu Sidoarjo Publisher can continue to exist and increase its sales